2019
DOI: 10.3390/ijms20102371
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels and Thermosensitivity: TRP, TREK, or Both?

Abstract: Controlling body temperature is a matter of life or death for most animals, and in mammals the complex thermoregulatory system is comprised of thermoreceptors, thermosensors, and effectors. The activity of thermoreceptors and thermoeffectors has been studied for many years, yet only recently have we begun to obtain a clear picture of the thermosensors and the molecular mechanisms involved in thermosensory reception. An important step in this direction was the discovery of the thermosensitive transient receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 101 publications
(275 reference statements)
0
57
0
Order By: Relevance
“…The TRP superfamily consists of the following six subfamilies, which are based on sequence homology: ankyrin-rich (TRPA1), vanilloid (TRPV1-6), canonical (TRPC1-7), melastatin-like (TRPM1-8), polycystin (TRPP2/3/5), and mucolipin (TRPML1-3) [57]. Their localization is ubiquitary, and they can be activated by a wide number of molecules and stimuli [56,58,59]. In endometrial biopsies, TRP expression levels have been reported to be differently down-and upregulated during the different phases of the menstrual cycle [60].…”
Section: Transient Receptor Potential (Trp) Channels and Endometriosismentioning
confidence: 99%
“…The TRP superfamily consists of the following six subfamilies, which are based on sequence homology: ankyrin-rich (TRPA1), vanilloid (TRPV1-6), canonical (TRPC1-7), melastatin-like (TRPM1-8), polycystin (TRPP2/3/5), and mucolipin (TRPML1-3) [57]. Their localization is ubiquitary, and they can be activated by a wide number of molecules and stimuli [56,58,59]. In endometrial biopsies, TRP expression levels have been reported to be differently down-and upregulated during the different phases of the menstrual cycle [60].…”
Section: Transient Receptor Potential (Trp) Channels and Endometriosismentioning
confidence: 99%
“…These studies have led to the identification of a number of ion channels activated by a wide spectrum of physical and chemical stimuli. Those activated by temperature belong to a superfamily of ion channels called transient receptor potential (TRP) channels [68,69]. Four TRP subtypes are activated by an increase in temperature and two TRP channels are activated by decreases in temperature [68].…”
Section: Neuronal Control Of Body Temperaturementioning
confidence: 99%
“…Those activated by temperature belong to a superfamily of ion channels called transient receptor potential (TRP) channels [68,69]. Four TRP subtypes are activated by an increase in temperature and two TRP channels are activated by decreases in temperature [68]. For example, TRPM8 is an ion channel that admits Ca2 + and Na + in response to moderate cold (10-25 • C), while several transient receptor potential cation channels (TRV) have been proposed to sense warmth including TRVP1, TRVP3, TRCP4 and TRVP2 [70].…”
Section: Neuronal Control Of Body Temperaturementioning
confidence: 99%
“…The study of TREK currents in native neurons is challenging because the activity of these channels is reduced at room temperature and atmospheric pressure [28][29][30]. We take advantage of the neuroprotective agent riluzole, which activates the three members of the TREK subfamily (TREK-1, TREK-2 and TRAAK (TWIK-related arachidonic acid-stimulated potassium channel)) [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%